Determinants of Economic Growth in Malaysia 1970-2010 - HUSSIN, Fauzi; ROS, Norazrul Mat; NOOR, Mohd Saifoul Zamzuri (Asian Journal of Empirical Research, 2013)
This paper investigates the determinants of economic growth in Malaysia. Trade openness, foreign direct investment, government development expenditure and gross fixed capital formation are used as indicators of economic growth.The study used time series data for the period 1970 to 2010. The Johansen and Juseliuscointegration approach was applied to determine the long-run relationship between the variables. The study found that trade openness and foreign direct investment have significant but negative impact on economic growth in short run. Our results also show that government development expenditure has the strongest effect on economic growth in Malaysia.